Erythropoietin induces production of hepatocyte growth factor from bone marrow mesenchymal stem cells in vitro. (January 2017) - Tari, Kaveh; Atashi, Amir; Kaviani, Saied; AkhavanRahnama, Mahshid; Anbarlou, Azadeh; Mossahebi-Mohammadi, Majid
Abstract: Background: Hepatocyte Growth Factor (HGF) plays a pivotal role in hematopoiesis, motility, growth and mobilization of hematopoietic stem/progenitor cells (HSPCs). HGF mainly is produced by bone marrow mesenchymal stem cells (BM-MSCs). MSCs express erythropoietin (EPO) receptor. In this study, we aimed to assess the effect of EPO on HGF secretion in BM-MSCs. Methods: The BM-MSCs treated with EPO (4 IU/ml) for 6, 24 and 48 h. HGF gene expression and protein level were assessed using quantitative real time PCR (qRT-PCR) and Enzyme-linked immunosorbant Assay. In order to show the effect of secreted HGF on migration of HSPCs, hematopoietic stem cells (HSCs) were isolated from cord blood and evaluated using transwell migration assay. Results: We observed a significant increase in level of HGF in cell supernatant after 48 h compared to control group (P < 0.05). Also, qRT-PCR results demonstrated a significant elevation in HGF expression level after 24 and 48 h treatment with EPO compared to control group (P < 0.05). Finally, migration assay results showed a significant increase in migration of HSCs in treated group after 48 h. Conclusion: Our data indicated that EPO may play an important role in stem cell mobilization through up regulating HGF in MSCs and inducing migration of HSCs.